2019
DOI: 10.1039/c9md00139e
|View full text |Cite
|
Sign up to set email alerts
|

Recent development of leucyl-tRNA synthetase inhibitors as antimicrobial agents

Abstract: This review summarizes the recent development of LeuRS inhibitors, focusing on biological activity, SARs, molecular docking studies and applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 95 publications
(107 reference statements)
0
27
0
Order By: Relevance
“…[31] Accordingly, our initial investigation towards the synthesis of ethyl 2-styrylquinoxaline-3-carboxylate (8) was conducted employing ethyl 2-methylquinoline-3-carboxylate (9) and benzaldehyde as substrates as shown in Scheme 1. The substrate 9 was readily synthesized in good yield based on the method described by Kumar et al [32] involving the condensation reaction of phenylene diamine (10) with N-bromosuccinimide and ethyl acetoacetate. However, when 9 was subjected to the condensation reaction with benzaldehyde under the reaction conditions as described in literature [31] using boiling acetic anhydride as the media followed by hydrolysis in pyridine water mixture, this was not the case in our hands and the reaction proceed very poorly, giving an intractable complex mixture, from which the desired 8 could not be separated in any appreciable yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] Accordingly, our initial investigation towards the synthesis of ethyl 2-styrylquinoxaline-3-carboxylate (8) was conducted employing ethyl 2-methylquinoline-3-carboxylate (9) and benzaldehyde as substrates as shown in Scheme 1. The substrate 9 was readily synthesized in good yield based on the method described by Kumar et al [32] involving the condensation reaction of phenylene diamine (10) with N-bromosuccinimide and ethyl acetoacetate. However, when 9 was subjected to the condensation reaction with benzaldehyde under the reaction conditions as described in literature [31] using boiling acetic anhydride as the media followed by hydrolysis in pyridine water mixture, this was not the case in our hands and the reaction proceed very poorly, giving an intractable complex mixture, from which the desired 8 could not be separated in any appreciable yield.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9] In this context, a review involving the development of leucyl-tRNA synthetase inhibitors as antimicrobial agents has been reported just recently by Zhang and coworker. [10] It is well known that quinoxaline ring system is an exceptional class of nitrogen-containing heterocycles present in many pharmacologically relevant molecules, and has been acted as a valuable pharmacophore for drug design in the field of contemporary medicinal chemistry. [11][12] In this regard, Ajani [13] described the status of quinoxaline motifs as excellent pathfinders in therapeutic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the remarkable selectivity of this scaffold and the feasibility or easily adding chemical modifications to it, AN2690 derivatives targeting other pathogens are being actively sought. Benzoxaborole derivatives have been shown to be great potential inhibitors against S. pneumoniae and T. brucei LeuRSs [ 169 ]. AN3365 (also known as GSK2251052) was developed as treatment for Gram-negative bacterial infections [ 170 ].…”
Section: Natural and Synthetic Aarss Inhibitors And Their Inhibitomentioning
confidence: 99%
“…by placing them under conditions in which the molecular defects associated with drug resistance are especially fitness-costly. For our drug model, we used tavaborole (also known as AN2690), a synthetic small-molecule inhibitor of protein synthesis [18][19][20] . In 2014, this drug was approved by the FDA to treat onychomycosis (nail fungus) 21 .…”
mentioning
confidence: 99%
“…In 2014, this drug was approved by the FDA to treat onychomycosis (nail fungus) 21 . Numerous studies have indicated that tavaborole and its chemical derivatives may also be of potential use against microbial pathogens, including Plasmodium falciparum 22,23 , Toxoplasma gondii 24 , Trypanosoma brucei [25][26][27][28][29] , Cryptosporidium parvum 24 , Staphylococcus aureus 30 , Mycobacterium tuberculosis [31][32][33][34] , Streptococcus pneumoniae 35 , and multidrug-resistant strains of Pseudomonas aeruginosa and Escherichia coli 20 .…”
mentioning
confidence: 99%